Winter tick sharing between ungulates in the Greater Yellowstone Ecosystem and implications for apparent competition - Troy Koser; Alynn Martin; Alyson Courtemanch; Laura Thompson; Benjamin Wise; Gary Fralick; Sarah Dewey; Amy Girard; Brandon Scurlock; Jared Rogerson; Kennan Oyen; Paul Cross (Ecosphere)
Abstract Host species heterogeneity can drive parasite dynamics through variation in host competency as well as host abundance. We explored how elk (Cervus canadensis) with apparent subclinical infestations of winter tick (Dermacentor albipictus) may be a cryptic reservoir and drive winter tick dynamics, impacting moose (Alces alces) populations. We found that winter tick infestation loads did not vary remarkably between both host species and winter ticks sourced from elk and moose produced similar numbers of larvae which activated within 5 days of each other. We also found similar larval densities in habitats predominately used by elk, moose, and both host species. Our analysis of 2793 informative single‐nucleotide polymorphisms showed genetic differentiation among tick populations that were only ~75 km apart, but fewer differences among ticks from elk or moose in the same locality, suggesting sharing of winter ticks across host species. Despite the clinical signs of high winter tick infestations being most apparent on moose, elk may be critical drivers of winter tick population dynamics and indirectly compete with moose in areas where they outnumber moose populations, a common characteristic of ungulate communities in western North America. Management interventions aimed at addressing winter tick issues on moose may wish to consider the movement patterns and abundance of cryptic reservoirs like elk.